Qur’anic Values-Based Character Education: Implementation of Discipline and Responsibility - Wulandari, Viona Dwi; Anwar, Fuady; Oktavia, Gifa; Rambe, Khairul Fadli (Institute of Research and Community Service STAI Yayasan Tarbiyah Islamiyah Kota Padang, 2025)
This study aims to analyze the implementation of character education focused on discipline and responsibility in Qur’anic educational institutions, as well as the factors influencing its success. The research employs a descriptive qualitative approach with a field study design, while data were collected through observation, interviews, and documentation involving teachers, students, and institution administrators. The findings indicate that the value of discipline is implemented through habituation practices such as punctual attendance, neat dressing, adherence to rules, and orderly completion of tasks. Meanwhile, the value of responsibility is manifested through active participation in learning activities, concern for the environment, and the fulfillment of entrusted duties. The character-building process is carried out through exemplary behavior, habituation, and continuous supervision by teachers. The supporting factors of character implementation consist of internal factors namely students’ motivation and self-awareness and external factors, including the role of teachers, family support, and the learning environment. These findings affirm that character education based on Islamic values plays a vital role in shaping a Qur’anic generation that is virtuous, disciplined, and responsible.nd policymakers in developing a more effective curriculum.